MANAGEMENT WITH THE UTILIZATION OF SOCIAL MEDIA WELLNESS TOURISM HEALTH TOURISM HOT SPRINGS HOT SPRING IN PENEBEL VILLAGE, TABANAN DISTRICT - Anak Agung Ari Sutraningsih (Ride: Journal of Cultural Tourism and Religious Studies, 2023)
Tourism was one of the main sectors long before the technological era 4.0. The current tourism model we find is quite varied with alternative tourism concepts such as religious and spiritual tourism, health tourism, educational tourism, cultural tourism, water tourism, tourism villages. In the past, before technology, as it is now, we can find tourism information through news, conventional information models that require an intermediary before we can enjoy the selected tour. Recent tourism issues related to the reduced role of humans in the provision of tourism services are caused by the very rapid development of information technology at present but not too significant in terms of the implications that occur. Currently, the role of social media information technology has replaced the role of verbal tourism management. But also the physical touch of the human role is still needed with the hospitality offered in this hospitality tourism industry. One model of Management by Utilizing Social Media Wellness Tourism Health Tourism Penatahan Hot Spring Penebel Village, Tabanan Regency. Using descriptive qualitative methods and literature studies, the latest tourism issues will be described in the era of information technology 4.0 regarding management by utilizing social media related to health tourism at Penatahan hot springs, where these tours are already widely available around it to0